Konsep Politik Legislasi Hukum Keluarga Di Indonesia - Jantarda Mauli Hutagalung; Tantri Gloriawati (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
The issue of family law based on Islamic law, concerning marriage, inheritance and so on which can not be equated with non-Muslims, is one reason for the importance of Islamic Family Law itself. The enactment of Law Number 1 of 1974 concerning Marriage and KHI (Compilation of Islamic Law) is the answer to the problem of the uncertainty and the demands of the Muslim community to be a guide, and a reference in overcoming problems surrounding family law. In this paper, we will discuss the Political Concept of Islamic Family Law Legislation. This is important, because every policy or law issued by the government, at the same time there is a long political process so that the policy reaches the people. As it is known that not all juridical products are in line with the aspirations of the people. There are juridical products that are considered by the community to be contrary to the enforcement of democracy. One of the causes is the intervention of political interests in the internal power.